Gambaran Pasien Tumor Palpebra RSUP Prof. dr. R. D. Kandou Periode Juni 2023 – Juni 2025 - Manoppo, Rillya; Kalalo, Peter; Sumual, Vera; Hartono, Yuliana; Akay, Freili (JURNAL KEPERAWATAN, 2026)
This study aims to determine the characteristics of patients with palpebral tumors at Kandou Hospital from June 2023 to June 2025. The type of study is a retrospective observational study using medical record data from Prof. dr. R. D. Kandou Hospital Manado from June 2023 to June 2025. The results obtained 145 patients with 38 patients (26.2%) in 2023, then became 62 patients (42.8%) in 2024, and increased to 45 patients (31%) in 2025. The majority male were 84 patients (57.9%), while female patients were 61 patients (42.1%). Most palpebral tumor patients in the age range of 40–50 years were 61 patients (42.1%). The nature of the palpebral tumors found benign was 93 cases (64.1%), while malignant tumors were recorded as 52 cases (35.9%). The conclusion was that 145 patients were mostly male (57.9%), aged 40-50 years (42.1%), and the most common tumor findings were benign tumor lesions (64.1%) with the type being dermoid cysts (28.3%).